Synthesis of Gold Nanoparticles by using Batch Method and Study its Antibacterial Activity - Ahmed Mohammed et al. (مجلة بغداد للعلوم, 2020)
The research involves preparing gold nanoparticles (AuNPs) and studying the factors that influence the shape, sizes and distribution ratio of the prepared particles according to Turkevich method. These factors include (reaction temperature, initial heating, concentration of gold ions, concentration and quantity of added citrate, reaction time and order of reactant addition). Gold nanoparticles prepared were characterized by the following measurements: UV-Visible spectroscopy, X-ray diffraction and scanning electron microscopy. The average size of gold nanoparticles was formed in the range (20 -35) nm. The amount of added citrate was changed and studied. In addition, the concentration of added gold ions was changed and the calibration curve was calculated used to estimate Au ions in different samples. The effectiveness of gold nanoparticles prepared according to Turkevich method was studied as antibacterial agents against E. coli bacteria. The minimum inhibition concentration of gold nanoparticles that inhibit bacterial growth was calculated using the broth dilution method, which is based on several dilutions to determine the inhibition concentration.